Development of electronic activity sheet based preview, question, read, reflect, recite, review (pq4r) learning strategy on ion balance and pH of buffer solution - R. Usman Rery; Erviyenni Erviyenni; Muhammad Agus Hardiyansyah (Pascasarjana Universitas Negeri Medan, 2022)
The development of a PQ4R-based electronic activity sheet on the material of ion balance and pH of the buffer solution aims to develop a valid electronic activity sheet and determine user responses in learning. The research method used is the research and development (R&D) method by applying a 4-D development model which includes Define, Design, Develop and Disseminate. Pandemic conditions cause research to only be carried out until the Develop stage which was followed by one-on-one trials, teacher trials, and limited trials. The data collection tools used were validity sheets and user response questionnaires. The data analysis technique used is to calculate the results of the validation percentage score and user response. The results of the study explain that the PQ4R-based electronic activity sheet developed has been categorized as